Studies in East Baltic consonant clusters 2: *rTv - Jakob, Anthony (Baltistica, 2025)
In this article, which is part of a series devoted to the investigation of consonant clusters in East Baltic, I examine the cluster *-rTv-. The main motivation for examining this cluster is a new etymological proposal: I suggest that Baltic *kirvja- ‘axe’ belongs to the root *kert- ‘to chop’. This is defended in Section 1, followed in Section 2 by a comparison with alternative proposals that start from roots of the shape *ker- and *kʷer-. In Section 3, I return to the cluster *-rTv-, identifying one probable and another potential parallel, and examine counter-evidence. In the course of the discussion, I also reassess the outcome of the cluster *dv in Baltic.